Apexification of an Immature Permanent Incisor with the Use of Calcium Hydroxide: 16-Year Follow-Up of a Case - Camila Maggi Maia Silveira; Cátia Cilene Nass Sebrão; Larissa Soares Reis Vilanova; Alfonso Sánchez-Ayala (Hindawi Limited, 2015)
Apexification is a process of forming a mineralized apical barrier and had been performed by using calcium hydroxide paste, due to its biological and healing performances in cases of existent trauma. This clinical report aims to report the results of a 16-year follow-up study of an apexification treatment applied to nonvital tooth 22 of a healthy 8-year-old male after a trauma. Clinical inspection of the tooth showed fractures of the incisal edge and mesial angle, absence of coronal mobility, and negative pulp vitality under cold testing. Radiographic analysis of the root revealed incomplete apex formation. The possibility of fracture into the root or luxation injury was rejected, and the diagnosis of pulp necrosis was verified. Apexification by calcium hydroxide and subsequent endodontic treatment were planned. Initial formation of the mineralized apical barrier was observed after 3 months, and the barrier was considered to be completed after 8 months. Clinical, radiographic, and CBCT examinations after 16 years verified the success of the treatment, although the choice of calcium hydroxide for apexification treatment is discussed.